Specific features of sedimentology in the outer part of the East Siberian Arctic Shelf; AGU Fall Meeting - 2015 - Dudarev O. V. Oleg Viktorovich; Gustafsson O. Orjan; Semiletov I. P. Igor Petrovich; Shakhova N. E. Nataljya Evgenjevna; Tesi T. Tommaso; Ruban A. S. Aleksey Sergeevich; Charkin A. N. Aleksandr Nikolaevich (2015, 2015)
Title screen